2020
DOI: 10.1007/s11092-020-09316-w
|View full text |Cite
|
Sign up to set email alerts
|

Aiding culturally responsive assessment in schools in a globalising world

Abstract: Across the world, teachers’ classroom assessment tasks and responsibilities are becoming more diverse due to increased migration. In this review, we address how migrant students are affected by assessment, both summative and formative, at the classroom level, with a focus on culturally responsive assessment (CRA). Previous research has shown that CRA practices mainly occur in student-centred classrooms. Furthermore, both student and teacher beliefs about teaching and learning might negatively affect migrant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 70 publications
(159 reference statements)
0
20
0
1
Order By: Relevance
“…Many of these strategies in each country can be subsumed as versions of formative assessment, such as 'self-assessment' or 'group performance', together with other types of performance, from pictorial to oral and written, hearing, reading and other formats. Generally, teachers who were competently working informed by a formative assessment philosophy seemed better equipped for culturally responsive assessment (Nortvedt et al 2020). In teaching second language learners, the concept of 'scaffolding' (Ovando et al 2003, p. 345) has spread to a number of classrooms.…”
Section: 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these strategies in each country can be subsumed as versions of formative assessment, such as 'self-assessment' or 'group performance', together with other types of performance, from pictorial to oral and written, hearing, reading and other formats. Generally, teachers who were competently working informed by a formative assessment philosophy seemed better equipped for culturally responsive assessment (Nortvedt et al 2020). In teaching second language learners, the concept of 'scaffolding' (Ovando et al 2003, p. 345) has spread to a number of classrooms.…”
Section: 21mentioning
confidence: 99%
“…A review of the research on teaching, learning, assessment and diversity revealed that there is a body of literature concerning the educational needs of students not belonging to the respective mainstream culture and about responsive pedagogies aiming to enhance their learning. Such issues have until now been more widely studied in North America and other English-speaking countries than in other European countries (Nortvedt et al 2020). Most of the previous research and conceptual work seems to focus on the implications of cultural and linguistic diversity for teaching and learning, rather than on assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on culturally responsive leadership is also informed by the fact that minority students, including students with a migration background, who are experiencing low academic achievement, are more likely to be experiencing behaviour issues in school and have a higher representation in special needs, compared to their peers (Vavrus and Cole, 2002;Gregory and Weinstein, 2008). A growing body of studies provides evidence that school leadership has a significant impact on student achievement (Beachum, 2011;Furman, 2012;Johnson, 2007) and, by association, students' achievement from a migration background (Nortvedt et al, 2020). Magno and Schiff (2010), in their study on successful culturally responsive leadership, highlight the fact that such leaders, firstly, make institutional adjustments to welcome and support immigrant students with the implementation of administrative procedures.…”
Section: Research Phase 1 Part 1: Making Meaning Of the Concept Of Culturally Responsive Leadershipmentioning
confidence: 99%
“…As a recommendation, a dire need exists to seek more effective ways to improve the expectations and beliefs related to the academic achievement of both teachers and Syrian students, despite the many barriers present in Turkey. That is because both students’ and teachers’ beliefs about teaching and learning might negatively affect the opportunities of refugee students to engage in assessment situations (Alefesha and Al‐Jamal, 2019; Woofter, 2019; Nortvedt et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to Nortvedt et al . (2020), teaching, learning and assessment practices should be aligned with and included in classroom norms to be culturally responsive.…”
Section: Discussionmentioning
confidence: 99%